2015
DOI: 10.1038/srep15954
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid (dexamethasone)-induced metabolome changes in healthy males suggest prediction of response and side effects

Abstract: Glucocorticoids are indispensable anti-inflammatory and decongestant drugs with high prevalence of use at ~0.9% of the adult population. Better holistic insights into glucocorticoid-induced changes are crucial for effective use as concurrent medication and management of adverse effects. The profiles of 214 metabolites from plasma of 20 male healthy volunteers were recorded prior to and after ingestion of a single dose of 4 mg dexamethasone (+20 mg pantoprazole). Samples were drawn at three predefined time poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 69 publications
8
76
4
Order By: Relevance
“…Synthetic GCs are largely used as anti-inflammatory drugs [163] and dexamethasone (Dex) was found to reduce EMT in colon cancer cells as well as in human peritoneal mesothelial cells [164,165]. However, long-term systemic exposure to Dex causes a variety of adverse effects [166], and novel strategies are needed to deliver Dex in cancer cells.…”
Section: Dexamethasonementioning
confidence: 99%
“…Synthetic GCs are largely used as anti-inflammatory drugs [163] and dexamethasone (Dex) was found to reduce EMT in colon cancer cells as well as in human peritoneal mesothelial cells [164,165]. However, long-term systemic exposure to Dex causes a variety of adverse effects [166], and novel strategies are needed to deliver Dex in cancer cells.…”
Section: Dexamethasonementioning
confidence: 99%
“…Functional sensitivity has been found to be 50 pg/mL and intermediate precision (CV) was 2.7% at 125 pg/mL (12 ). Metabolite profiling of human plasma samples was performed at metanomics GmbH using both GC-MS (Agilent 6890 GC coupled to an Agilent 5973 MS-System) and LC-MS/MS systems (Agilent 1100 HPLC-System coupled to an Applied Biosystems API4000 MS/MS-System) as previously described (13 ). In addition, a dedicated analytical protocol was developed for the routine determination of specific metabolomic features.…”
Section: Laboratory Analysis and Metabolite Profilingmentioning
confidence: 99%
“…As the tricarboxylic acid cycle (TCA) cycle is the basis for biological metabolism and is the hub of carbohydrate, fatty acid, and amino acid metabolism pathways1718, which is related to growth and competition of T. asperellum GDFS1009, corresponding RNA-seq data of 24 h and 48 h cultures was analyzed and the results showed that, compared to the control T. asperellum GDFS1009, T. asperellum GDFS1009 treated with validamycin A had only increased aconitase, but not the rate-limiting enzymes. GC-MS metabolomics 24 h data analysis showed that, in T. asperellum GDFS1009 treated with validamycin A and control, the yield of citric acid, succinate, and malic acid was not significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…Specific analysis about TCA cycle, G protein-MAPK-cAMP signaling pathway was via JGI (Joint Genome Institute) online blast with related reference genes, and the highest homology genes were selected for the expression analysis based RNA-seq data and drawing diagrams1718192035.…”
Section: Methodsmentioning
confidence: 99%